Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5603/20320
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of apoptotic factors, cytokeratins, and metalloproteinase-9 in periapical and epithelialized gingival lesions

Abstract: Abstract:The aim of the study was to assess the involvement of apoptotic factors, cytokeratins and metalloproteinase-9 in the histogenesis of both Epithelialized Gingival Lesions (EGL) and Periapical Lesions (PAL). 55 consecutive patients, 30 with PAL and 25 with EGL, were selected for the study after clinical and radiological examinations. The PAL patients had severe periapical lesions and tooth decay with exposure of the pulp chamber. All PAL and EGL biopsies were surgically extracted, fixed in 10% buffered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Taking together these previous and present results, it is reasonable to suggest that both the extrinsic and intrinsic pathways might have been involved in the cyclic stretch-induced apoptosis in PDL cells, but functioned differently in the apoptosis induced by 6 and 24 h stretches respectively. As to in vivo situation, Tu et al and Leone et al reported the results of immunohistochemistry analysis suggesting the presence of caspase-9 in gingivae from SD rats and from human tissue, respectively [27, 28]. With respect to caspase-8, though there were no published studies showing in situ labelling for caspase-8 in periodontal tissue, the caspase-8 immunohistochemically positive fibroblast-like cells have been observed in human implant interface membrane [29].…”
Section: Discussionmentioning
confidence: 99%
“…Taking together these previous and present results, it is reasonable to suggest that both the extrinsic and intrinsic pathways might have been involved in the cyclic stretch-induced apoptosis in PDL cells, but functioned differently in the apoptosis induced by 6 and 24 h stretches respectively. As to in vivo situation, Tu et al and Leone et al reported the results of immunohistochemistry analysis suggesting the presence of caspase-9 in gingivae from SD rats and from human tissue, respectively [27, 28]. With respect to caspase-8, though there were no published studies showing in situ labelling for caspase-8 in periodontal tissue, the caspase-8 immunohistochemically positive fibroblast-like cells have been observed in human implant interface membrane [29].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis in the epithelium of periapical lesions has been confirmed by the expression of Bcl‐2 or caspase‐3 . The expression of caspase‐9 has been studied only once, in 20 epithelialised lesions of periapical and gingival origin, showing strong immunoreactivity in high levels in both lesion types . This study did not clarify whether the ‘periapical lesions’ included true radicular cysts or periapical granulomas with epithelial cells.…”
Section: Discussionmentioning
confidence: 92%
“…When the cell has run out of ATP, the ATPase cannot function properly; this leads to an uncontrolled influx of calcium ions from the intercellular space into the cell. The expression of caspase-9 has been studied only once, in 20 epithelialised lesions of periapical and gingival origin, showing strong immunoreactivity in high levels in both lesion types (18). The up-regulation of calcium into the mitochondrion results in the release of cytochrome c, which is also transferred into the cytoplasm via the VDAC channel.…”
Section: Discussionmentioning
confidence: 99%